2020
DOI: 10.1016/j.lanwpc.2020.100042
|View full text |Cite
|
Sign up to set email alerts
|

Community-based management of epilepsy in Southeast Asia: Two intervention strategies in Lao PDR and Cambodia

Abstract: Background Epilepsy affects more than 50 million people worldwide, 80% of whom live in low- and middle-income countries (LMICs). In Southeast Asia, the prevalence is moderate (6‰), and the main public health challenge is reducing the treatment gap, which reaches more than 90% in rural areas. Methods This 12-month comparative study (intervention vs. control areas) assessed the community effectiveness of two different strategies for the identification and home follow-up o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Home‐care has been applied to improve outcomes in chronic medical disorders, notably hypertension, with mixed results 30 . It has also been implemented for epilepsy previously, e.g., in Kenya, Laos and Cambodia 12,31–33 . The studies from communities in Laos and Cambodia used facility‐ and community‐based health visitors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Home‐care has been applied to improve outcomes in chronic medical disorders, notably hypertension, with mixed results 30 . It has also been implemented for epilepsy previously, e.g., in Kenya, Laos and Cambodia 12,31–33 . The studies from communities in Laos and Cambodia used facility‐ and community‐based health visitors.…”
Section: Discussionmentioning
confidence: 99%
“…30 It has also been implemented for epilepsy previously, e.g., in Kenya, Laos and Cambodia. 12,[31][32][33] The studies from communities in Laos and Cambodia used facility-and community-based health visitors. Our model encompassed home-care provided by the community-and primary care providers with backup by neurologists.…”
Section: Sensitivity Analysesmentioning
confidence: 99%
“…These findings are similar to other authors who found that epilepsy is characterized by recurring seizures that can be accompanied by unconsciousness and loss of bowel or bladder function stiff muscles, uncontrollable jerking movements of the arms and legs, dizziness, and anxiety are all symptoms of epilepsy. 29,30 Epilepsy was diagnosed as a result of these observations. Furthermore, a study conducted by Nass, 31 Stutton 32 shows that epilepsy can be identified with basic blood tests (complete blood count, urea, creatinine, electrolytes, liver function tests, and glucose).…”
Section: Diagnosis Of Epilepsymentioning
confidence: 97%
“…The reduction in epilepsy TG in the rural areas of the Bolivian Gran Chaco has been the main aim of different projects performed by our group over the last 20 years in this area [11] , [12] , [13] , [14] , [15] , [16] . In agreement with the WHO guidelines [17] , and likewise other campaigns carried out in other LMIC [18] , [19] , during our long-lasting activity in rural Bolivia, we performed several epidemiological and interventional surveys including an anthropological survey, training programs directed to General Practitioners (GPs), nurses and Community Health Workers (CHWs) of the rural communities of the Chaco region as well as communities awareness programs [13] , [14] , [15] . These activities have increased the level of knowledge and awareness about epilepsy in this region, and facilitated the access to care leading to a reduction in the TG in this area [20] .…”
Section: Introductionmentioning
confidence: 99%